Are Authors of Industrial Property Encouraged? (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the problems associated with encouraging authors of industrial property objects, with an emphasis on stimulating creative activity. Obstacles are analyzed, such as the lack of financial and organizational support in the early stages of development and protection, as well as the difficulty of obtaining patents and licenses, which can negatively affect the motivation of authors. It also raises the issue of unfair rewards and limitations of incentive programs, which can lead to a decrease in motivation in the innovation field. The experience of legal decisions in the academic field is analyzed and improvements to the legislation are proposed to improve incentives for authors.